RELATIONSHIP BETWEEN DISCHARGE PLANNING AND PATIENT SATISFACTION IN CHRONIC KIDNEY DISEASE PATIENTS - Ghea Griselda Priyosaputro; Indah Mawarti; Luri Mekeama (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Discharge planning is an important component of nursing care that prepares patients to continue self-care after hospitalization. In Chronic Kidney Disease (CKD) patients, effective discharge planning is needed because they require continuous treatment, adherence to therapy, and lifestyle modifications. Proper implementation of discharge planning is expected to improve nursing service quality and patient satisfaction. This study aimed to determine the relationship between discharge planning implementation and patient satisfaction among Chronic Kidney Disease (CKD) patients in the Internal Inpatient Ward of Raden Mattaher Hospital, Jambi. This study used a quantitative design with a cross-sectional approach. The population included all CKD patients hospitalized in the Internal Inpatient Ward of Raden Mattaher Hospital, Jambi. A total of 50 respondents were selected using purposive sampling. Data were collected through discharge planning and patient satisfaction questionnaires. Data analysis was performed using the Spearman Rank correlation test. The results showed that 62.0% of respondents assessed discharge planning implementation as moderate, while 38.0% considered it poor. Patient satisfaction was mostly categorized as moderate (98.0%), and only 2.0% of respondents reported being satisfied. The Spearman Rank test showed a p-value of 0.205 with a correlation coefficient of r = -0.182, indicating no significant relationship between discharge planning implementation and patient satisfaction, with a very weak negative correlation. The implementation of discharge planning was not significantly associated with patient satisfaction among CKD patients in the Internal Inpatient Ward of Raden Mattaher Hospital, Jambi. These findings highlight the need for continuous evaluation and improvement of discharge planning practices to optimize nursing care quality